GROWTH OF FOUR MULTIPURPOSE TREES - Paulo Sérgio Lima e Silva; Kathia Maria Barbosa e Silva; Janilson Pinheiro de Assis; Nilzemary Lima da Silva (Revista Caatinga, 2007)
The mesquite (Prosopis juliflora), jucá (Caesalpinia ferrea), white popinac (Leucaena leucocephala) and tamar ind (Tamarindus indica) are useful species for the Brazilian semi-arid region because are sources of wood, f i rewood, fruits, forage and others products. Measuring plant height (y) i n t rees may not be an easy task, but canopy (x) and stem diameter (z) can be more eas ily evaluated. This work¿s object ive was two-fold: evaluate the growth of related species , in the f i r s t two years of age , and obtain l inear equations to est imate y from x or z, and x from z, in those species. A randomized complete block design with four t reatments (trees) and eight replications was used. The values for x, z, and y were measured biannually from October/2003 to March/2005. The species had different growth in te rms of plant height and stem and canopy diameters. Twenty-four months after the transplantation, the highest growth regarding these t rai t s was observed i n the mesquit e (as wel l as jucá, as the plant height ). The bes t equations (based on the R2 value) to est imate y in mesquite, jucá, white popinac and tamarind are: y = 0,33 + 0,05 z, y = 0,70 + 0,06 z, y = 0,64 + 0,04 z and y = 0,06 z, respectively. The equations to estimate x from z are: x = 1,47 + 0,03 z, x = 0,55 + 0,05 z, x = 0,04 z e x = 0,05 z , respectively, for the same species.